Improving the quality and safety of fish paste through education and implementation of CPPOB in Situbondo Regency - Cecilia Eny Indriastuti; Dewi Sarastani; Ima Kusumanti; Tetty Barunawati Siagian; Brigitta Indah Permata (Community Empowerment, 2024)
One of the major challenges in maintaining the quality of food products at the micro, small, and medium enterprise (MSME) scale today is meeting food safety standards. Food safety encompasses the entire process from preparing raw materials to production and reaching consumers. However, some MSME players still lack an understanding of food quality and safety standards, which can directly impact product quality and safety. The aim of the community service activities is to gather data and provide an understanding of food safety knowledge. Methods used include data collection, education, focus group discussions (FGD), as well as pre-test and post-test evaluations of members of the Panarukan MSME group in Wringinanom Village, Panarukan District, Situbondo Regency, East Java. The results of this community service activity include data on the business scale, with the majority being micro businesses, as well as an 11.11% increase in food safety knowledge.